Selected Case From the Arkadi M. Rywlin International Pathology Slide Seminar: Atypical Thymoma With Rhabdomyomatous Differentiation. (January 2019) - Suster, David; Epstein, Howard D.; Pearlstein, Daryl; Suster, Saul
Abstract : Thymic epithelial neoplasms with foci of rhabdomyomatous differentiation are rare. A case is presented of a primary thymic epithelial neoplasm showing the features of an atypical spindle cell thymoma that contained foci of bland-appearing rhabdomyomatous cells. The histologic and immunohistochemical features of this tumor are discussed along with a review of the literature and the comments from the AMR members to the case.